The link between social communication and mental health from childhood to young adulthood: A systematic review - Dall, Magdalena; Fellinger, Johannes; Holzinger, Daniel (Frontiers in Psychiatry, 2022)
This systematic review investigates the current state of the literature on the association between social communication (SC) skills and mental health outcomes in children and young adults. We ran searches using terms describing SC and mental health in the following databases: PubMed, the Psychology and Behavioral Sciences Collection, APA PsychInfo, the Education Resource Information Center (ERIC) and the Cumulative Index to Nursing and Allied Health Literature (CINAHL). We included studies that both measured SC before age 21 years and assessed a mental health component, such as behavior/conduct problems, anxiety, depression, or emotional problems, before age 30. Only peer-reviewed articles published in or after 2000 were retained. In total, 27 studies were included in the narrative synthesis. Overall, the methodological quality was good. A longitudinal design was used in 12 studies, seven of which sourced data from the Avon Longitudinal Study of Parents and Children. Most studies investigated the broad concept of pragmatic language and its influence on internalizing, externalizing, and peer-relationship problems. The analyzed works included population-based studies and studies investigating special populations with existing mental health problems or at increased risk of developing them. The population-based cross-sectional studies showed significantly higher rates of SC problems in children with mental health problems while those with a longitudinal design found earlier onset and more persistent mental health problems in children who had the most severe SC difficulties. Studies with special populations confirmed more SC problems as compared to typically developing children and worse mental health outcomes in children with additional SC difficulties. The available literature thus shows consistently significant, mostly moderate associations between SC skills and mental health outcomes. SC difficulties earlier in life can predict mental health problems and impact their trajectories.